Collected writings of John Maynard Keynes Vol XV Activities 1906-1914 India and Cambridge - Johnson, Elizabeth (Ed.); Keynes, John Maynard (Cambridge Cambridge University Press, 2013)
From the India office to Cambridge 1906-1913